Effect of propofol and ciprofol in patients undergoing bronchoscopy: protocol for a double-blind, randomised controlled trial - Fang Chen; Cheng Li; Dongliang Li; Jinxuan Tang; Jiayu Huang (BMJ Open)
Introduction Propofol is a fast-acting intravenous anaesthetic widely used for sedation and anaesthesia in gastrointestinal endoscopy, bronchoscopy, and the induction/maintenance of general anaesthesia in outpatients and inpatients; however, propofol has several undesirable effects, including injection pain, which affects the physical and mental health of patients, and cardiopulmonary depression, characterised by hypotension, bradycardia and apnea, which commonly occur in clinical practice. Ciprofol (HSK3486) is a propofol analogue with good clinical safety, high potency and some advantages over propofol, including lower injection pain and haemodynamic depression in patients undergoing gastroscopy and colonoscopy. This study aims to compare the impact of equivalent effective doses of propofol and ciprofol on haemodynamic changes in patients undergoing bronchoscopy under general anaesthesia.Methods This prospective, double-blind, randomised, controlled clinical trial will recruit 250 patients aged 18–80 years scheduled for elective bronchoscopy under general anaesthesia. The cohort will be randomised into two groups in a 1:1 ratio: propofol (200 mg/20 mL of saline) and ciprofol (40 mg/20 mL of saline). The primary outcomes are changes in heart rate and blood pressure before and after induction, laryngeal mask airway (LMA) placement and bronchoscopy placement. The secondary outcomes are the incidence of choking and injection pain, the type and dose of vasoactive drugs used during the operation, and the level of postoperative satisfaction among surgeons, anaesthesiologists and patients.Ethics and dissemination This trial was approved by the Medical Ethics Committee of Shanghai Fourth People’s Hospital, School of Medicine, Tongji University and registered with the Chinese Clinical Trials Registry (Identifier: ChiCTR2200063048) on 29 August 2022. The findings of this study will be disseminated through various channels. Academic dissemination will include publication in peer-reviewed journals and presentations at national and international conferences.Trial registration number ChiCTR2200063048.